Sistema de irrigación utilizando IoT para cultivos de la Universidad Nacional de Loja Irrigation system using IoT for crops at the National University of Loja. - Minga Medina, Angel Favian (2023)
Currently, the Internet of Things (IoT) has had a significant impact on the development of technological solutions, enabling various real-world components to connect to the Internet and allowing interaction with them. There are extensive applications for process automation in various fields. One such application where IoT can be implemented is agriculture, known as Smart Farming, which improves agricultural processes, such as irrigation a vital process for crops. With IoT, it becomes possible to monitor the water needs of plants based on data sent by sensors, enabling better control of water usage. In this context, the objective of this research work is to develop a prototype IoT irrigation system for crops at the Universidad Nacional de Loja. This work introduces the use of hygrometer sensors to capture soil moisture changes, triggering irrigation when the soil moisture reaches the permanent wilting point and shutting off irrigation when it reaches field capacity. The methodological framework used consisted of three phases. I) A systematic literature review (SLR) was conducted to gather relevant information on the topic and address the research questions. II) The software solution was developed using the XP methodology, applying standards such as the IEEE-830 document to specify software requirements and the 4+1 architectural document. III) An experimentation phase was carried out to understand the functioning of the sensors and the data they send based on soil moisture at specific times. Finally, the prototype development was executed in an academic environment, starting with the SLR phase, which yielded 25 articles, most of which utilized a three-layer architecture for irrigation system automation, employing the MQTT communication protocol through the mosquitto tool, which functions as a server or broker for packets sent from publishers to subscribers. The three-layer architecture was adapted to the prototype design for irrigation control, and the control module was developed using the agile XP software methodology, followed by the assembly of the prototype using information gathered in the previous phases. In this way, a prototype IoT irrigation system was developed, capable of capturing soil moisture using hygrometer sensors to determine when it is necessary to open and close the irrigation system. Keywords: Internet of Things, software, prototyping, irrigation, automation, Smart farming